El castillo de la pureza: A love story? - Medina Ávila, Virginia (2020)
The movie El castillo de la pureza, by Arturo Ripstein (1972), is based on a real event that took place in Mexico City in 1959. The objective of the article is to describe the context of the event, inscribed in the police annals of the Mexican Capital and how such a sordid story (according to our perspective) could be adapted to the screen as a “love story”, highlighting the work of the screenwriter José Emilio Pacheco (JEP). A first reading of the film shows us the confinement of a family (forced by the father) and that the isolation from the outside world is accepted by the wife as an almost divine plan of the one who loves and respects blindly. Our intention is to deepen this view by offering an analysis of the information from the press of the time,from excerpts from the script, as well as scenes from the film and the frames corresponding to the chosen sequence that I have named “Preamble to the crisis. The tranquility in the castle begins to crack”.